2019
DOI: 10.1126/sciadv.aau4065
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of fault slip by fluid injection in the laboratory and in situ

Abstract: Faults can slip seismically or aseismically depending on their hydromechanical properties, which can be measured in the laboratory. Here, we demonstrate that fault slip induced by fluid injection in a natural fault at the decametric scale is quantitatively consistent with fault slip and frictional properties measured in the laboratory. The increase in fluid pressure first induces accelerating aseismic creep and fault opening. As the fluid pressure increases further, friction becomes mainly rate strengthening, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
215
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(258 citation statements)
references
References 51 publications
(90 reference statements)
21
215
0
Order By: Relevance
“…While these temperatures could be interpreted to be near the brittle-ductile transition for quartz-bearing rock (e.g., Scholz, 1988), this is unlikely given that seismicity at the nearby (and lithologically similar) Rotokawa geothermal field occurs in host rock with measured temperatures in excess of 330 • C . In addition, recent results have shown that a significant portion of induced seismicity may be triggered not by pore pressure perturbation, implying hydraulic connection to a wellbore, but by static and dynamic stress transfer onto suitably oriented fractures outside the reservoir (e.g., Cappa et al, 2019;Riffault et al, 2018). In addition, recent results have shown that a significant portion of induced seismicity may be triggered not by pore pressure perturbation, implying hydraulic connection to a wellbore, but by static and dynamic stress transfer onto suitably oriented fractures outside the reservoir (e.g., Cappa et al, 2019;Riffault et al, 2018).…”
Section: Event Locationmentioning
confidence: 99%
See 3 more Smart Citations
“…While these temperatures could be interpreted to be near the brittle-ductile transition for quartz-bearing rock (e.g., Scholz, 1988), this is unlikely given that seismicity at the nearby (and lithologically similar) Rotokawa geothermal field occurs in host rock with measured temperatures in excess of 330 • C . In addition, recent results have shown that a significant portion of induced seismicity may be triggered not by pore pressure perturbation, implying hydraulic connection to a wellbore, but by static and dynamic stress transfer onto suitably oriented fractures outside the reservoir (e.g., Cappa et al, 2019;Riffault et al, 2018). In addition, recent results have shown that a significant portion of induced seismicity may be triggered not by pore pressure perturbation, implying hydraulic connection to a wellbore, but by static and dynamic stress transfer onto suitably oriented fractures outside the reservoir (e.g., Cappa et al, 2019;Riffault et al, 2018).…”
Section: Event Locationmentioning
confidence: 99%
“…The advance of the induced pressure front is controlled by the hydraulic diffusivity of the reservoir (also referred to as transmissivity, the permeability thickness product: kh), which is closely linked to the reservoir permeability. However, a variety of mechanisms are responsible for triggering seismicity, many of which are unrelated to the hydraulic properties of the reservoir, leading to speculation as to the utility of SBRC (Cappa et al, 2019;Riffault et al, 2018). At Ngatamariki, and at most other naturally fractured reservoirs, flow is strongly influenced by the spacing and permeability of fractures (Grant & Bixley, 2011).…”
Section: Nm08 Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…While previous studies have provided overall knowledge of the ambient stress field in Oklahoma and southern Kansas, a high‐resolution stress map is needed to systematically assess fault criticality under the local stress field. This is especially important with the growing evidence that poroelastic stress (e.g., Barbour et al, ; Deng et al, ; Goebel et al, ; Segall & Lu, ) and aseismic creep propagation (e.g., Cappa et al, ; Eyre et al, ) could, in part, drive some of the induced seismicity. In this study, we develop a stress map with relatively high spatial resolution using a suite of 2,047 focal mechanism solutions obtained from Oklahoma and southern Kansas, allowing for more precise quantitative analysis of the fault stress state.…”
Section: Introductionmentioning
confidence: 99%